2017
DOI: 10.1103/physrevb.95.214514
|View full text |Cite
|
Sign up to set email alerts
|

Electron-phonon superconductivity in the filled skutterudites LaRu4P12, LaRu4As12 , and

Abstract: We have reported on the structural, elastic, electronic, lattice dynamical and electron-phonon interaction properties of LaT 4 X 12 (T = Ru, Pt and X = P, As, Ge) by using the generalized gradient approximation of the density functional theory and the plane-wave pseudopotential method. These lanthanum-filled skutterudites are found to be characterized with a flat band, resulting in a sharp peak in the electronic density of states, near the Fermi level. The lattice dynamical properties of these materials change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
4
4
0
Order By: Relevance
“…In the light of these results, we can suggest that Ru d and P p states dominate the conductivity of this filled skutterudite. It is worth to note that a similar observation has been made for LaRu 4 P 12 in our previous ab initio calculations [29].…”
Section: Structural and Electronic Propertiessupporting
confidence: 86%
See 1 more Smart Citation
“…In the light of these results, we can suggest that Ru d and P p states dominate the conductivity of this filled skutterudite. It is worth to note that a similar observation has been made for LaRu 4 P 12 in our previous ab initio calculations [29].…”
Section: Structural and Electronic Propertiessupporting
confidence: 86%
“…Filled skutterudite pnictides with the general formula LnT 4 X 12 (Ln = Lanthanide, T = Transition metal, X = Pnictogen) have received great attention since they exhibit a variety of individual properties, such as semiconducting [1][2][3][4], metal-insulator transition [5][6][7][8], different magnetic ordering [9][10][11][12][13][14], good thermoelectricity [15][16][17][18], heavy fermion behavior [19,20] and topological insulator behavior [21,22]. Furthermore, the La-based skutterudite compounds have received special interest due to their superconducting properties [23][24][25][26][27][28][29]. In particular, LaOs 4 P 12 and LaOs 4 As 12 exhibit superconductivity below 2.0 and 3.2 K, respectively [23,25].…”
Section: Introductionmentioning
confidence: 99%
“…Although these compounds have two electron-like and one holelike FS in common, independently of the theoretical scenario used, the hole pockets at Γ point are dependent on the theoretical scenario we used in our calculations. Thus, comparison of our theoretical predictions with de Hass van Alphen [70][71][72] experiments for LaPt 4 Ge 12 and PrPt 4 Ge 12 27 and new experiments for CePt 73 showed that these compounds are phonon-mediated superconductors. Thus, besides the average electron-phonon coupling in lanthanum filled-skutterudite 73 , it would be interesting to calculate electron-phonon couplings for each FS in other filled-skutterudite compound.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, comparison of our theoretical predictions with de Hass van Alphen [70][71][72] experiments for LaPt 4 Ge 12 and PrPt 4 Ge 12 27 and new experiments for CePt 73 showed that these compounds are phonon-mediated superconductors. Thus, besides the average electron-phonon coupling in lanthanum filled-skutterudite 73 , it would be interesting to calculate electron-phonon couplings for each FS in other filled-skutterudite compound.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation